ANALISIS 'KALA' DAN 'ASPEK' DALAM BAHASA JEPANG (Analisis kalimat dalam novel "Tokyo Fusen Nikki" - Catatan Harian Perahu Layar Tokyo- Karya Midori Nakano) - Darjat Darjat (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2009)
The term tense in Japanese is called by jisei. According to Nitta Yoshio (1976), tense or jisei is a grammatical framework that is related to an action happened, on going, and will take place in some framework of time. Meanwhile, the term aspect that is called by so or asupekuto, is a linguistic framework to elucidate an action processed within point in time. Aspect and tense marker are commonly similar to some other languages, for instance: a morphological change in its formation or the emergence of some other words as a lexical marker. This study discusses about the appearance of aspect and tense in Tokyo Fuusen Nikki (Note of a Tokyo Sailing Boat) written by Midori Nakano in 1993.